2021
DOI: 10.1007/s40825-021-00203-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of SO2 and SO2/SO3 Poisoning and Regeneration of Cu/BEA and Cu/SSZ-13 for NH3 SCR

Abstract: Two copper-exchanged zeolites, Cu/SSZ-13 and Cu/BEA, were studied as catalysts for the selective reduction of NOx by NH3 (NH3-SCR). Their activities for standard SCR (NOx = NO) and fast SCR (NOx = 50% NO + 50% NO2) were measured before and after sulfur poisoning at 250 °C. The effect of 30 ppm SO2 and a mixture of 24 ppm SO3 + 6 ppm SO2 was evaluated. The repetition of subsequent activity measurements served as regeneration method in SCR conditions. SO2 deactivated Cu/SSZ-13 whereas Cu/BEA was only moderately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…The Cu/SSZ-13 sample deactivates slower during SO 2 exposure than the other two catalysts but reaches a lower conversion during time on stream (see Figure S15, SI). These results are in line with the recent study by Auvray et al 32 where it was reported that Cu/BEA was significantly less affected than Cu/SSZ-13 from SO 2 or SO 3 , and the reason for this was suggested to be less steric hindrance of Cu/BEA by sulfur species.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
“…The Cu/SSZ-13 sample deactivates slower during SO 2 exposure than the other two catalysts but reaches a lower conversion during time on stream (see Figure S15, SI). These results are in line with the recent study by Auvray et al 32 where it was reported that Cu/BEA was significantly less affected than Cu/SSZ-13 from SO 2 or SO 3 , and the reason for this was suggested to be less steric hindrance of Cu/BEA by sulfur species.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
“…Contrary to the results shown above and the associated literature discussed, here the hydrothermal aging treatment did not mitigate the extent of SO 3 poisoning. Literature has consistently shown that SO 3 leads to a higher level of SCR catalyst deactivation compared to SO 2 , 34,36,59 with one explanation being higher levels of copper sulfate formation. 34 Our results show a similar trend in that the extent of SO 3 poisoning is higher compared to SO 2 poisoning, see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One important finding is that the presence of HSO 4 (NH 4 ) hinder O 2 adsorption in Cu-CHA. The structure of the zeolite has been measured to affect the SO 2 -induced deactivation [56,24]. Recently, the poisoning with SO 2 and SO 3 of Cu-CHA was compared to poisoning of Cu-BEA [24].…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the zeolite has been measured to affect the SO 2 -induced deactivation [56,24]. Recently, the poisoning with SO 2 and SO 3 of Cu-CHA was compared to poisoning of Cu-BEA [24]. It was observed that the deactivation of Cu-CHA was more severe than that of Cu-BEA even if Cu-CHA accumulated only 10 % of the sulfur accumulated in Cu-BEA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation